Antibodies to skeletal muscle actin and their reactivity with malignant melanoma of the choroid. Issue 3 (March 1980) - Malaty, A; Rahi, A; Garner, A
Abstract : Imprints of choroidal malignant melanoma cells were treated with serum containing antibodies to a purified preparation of actin derived from skeletal muscle. Evidence of a positive reaction, as shown by indirect immunofluorescence, substantiated an impression based on morphological criteria that choroidal melanoma cells contain actin protein. The significance of this protein in tumour biology is discussed, and a possible interference by antiactin antibodies in the immunodiagnosis of choroidal melanoma is highlighted.